Swear Words as Sociolinguistic Tools of Social Criticism in Jawaban Alina by Seno Gumira Ajidarma - Hasanah, Dina Fitria; Rahman, Adenarsy Avereus; Azizah, Hilma Azmi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines swear words as a form of social criticism in the short story “Jawaban Alina” by Seno Gumira Ajidarma, read by Dian Sastrowardoyo. Swear words, generally considered rude and impolite, may serve both aesthetic and rhetorical functions in literature. The data were collected from a transcription of the spoken performance, analyzed using qualitative content analysis within a sociolinguistic framework. The study specifically investigates how swear words function as linguistic strategies of resistance and emotional expression that reflect social inequality. The results show that swear words in this short story function as expressions of protest, emotional assertion, and satire against social injustice. The analysis highlights the connection between sociolinguistic theory and social criticism, emphasizing that linguistic choice can reveal social tension and ideological struggle in literary texts.